Tinjauan Yuridis Perlindungan Konsumen Terhadap Pangan Olahan Impor Tanpa Izin Edar: Studi Kasus Pemusnahan Satu Ton Roti Milk Bun Asal Thailand - Natalia, Imelda Hera; Prasetyo, Handoyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In February 2024, Bea Cukai Soekarno-Hatta with Badan Pengawas Obat dan Makanan has (BPOM) destroyed one ton of imported processed food namely milk buns from Thailand. There are two problems in this research, that’s how the distribution permits for imported processed food are regulated in Indonesia and how consumer protection for imported processed food without a distribution permit based on a case study of the destruction of one ton of Milk Bun bread from Thailand. The type of research is normative juridical. The problem approaches used are the statute approach and the case approach. Data sources were obtained from secondary data. The sources of legal materials are obtained from primary and secondary legal materials. The data collection techniques were carried out using library research. The data analysis technique was carried out using qualitative analysis. Meanwhile, analyzing legal materials is done using content analysis. The research results explain that the regulations for distribution permits for imported processed food in Indonesia is Peraturan Badan Pengawas Obat dan Makanan Nomor 27 Tahun 2022 tentang Pengawasan Pemasukan Obat dan Makanan Ke Dalam Wilayah Indonesia. The consumer protection against imported processed food without a distribution permit based on a case study of the destruction of one ton of milk bun bread from Thailand is BPOM gave orders to the Ditjen Bea Cukai, specifically Bea Cukai Soekarno-Hatta to carry out the destruction.